Financial Management and Marketing Technology as Drivers of MSME Performance - Syarif, Arman; Gumay, Nanda Fathiyah (Penerbit Goodwood, 2025)
Purpose: This study aims to examine the influence of financial management (FM) and marketing technology (MT) on the performance of micro, small, and medium enterprises (MSMEs) in Kotabumi, North Lampung, Indonesia. It specifically investigates whether FM and MT individually and jointly affect MSME performance in a resource-constrained setting. Methodology: A quantitative survey was conducted with 100 MSME owners as respondents. Data were analyzed using SmartPLS 3 and the partial least squares structural equation modeling (PLS-SEM) technique. This approach was selected because it is well suited for relatively small samples and complex causal models. Results: The findings indicate that FM did not have a significant direct effect on MSME performance, reflecting limited formal financial practices and constrained access to financial resources among local MSMEs. In contrast, MT showed a strong positive effect, highlighting its role in expanding market reach, improving competitiveness, and strengthening customer engagement. Furthermore, the combined effect of FM and MT explained 48.7% of performance variance, suggesting that FM supports the sustainability of MT adoption even if its individual effect is weak. Conclusion: Marketing technology significantly enhances MSME performance, while financial management plays a complementary enabling role. The findings suggest prioritizing digital adoption alongside progressive financial capability building in resource-constrained contexts. Limitations: The study was limited to one region with a relatively small sample, and it adopted a cross-sectional design. Other performance-related factors, such as innovation capability or entrepreneurial orientation, were not included. Contribution: This research contributes to the literature on MSME development and the resource-based view (RBV) by showing how marketing technology dominates short-term performance, while financial management plays a supportive role.